Antiracist Writing Assessment Ecologies Teaching and Assessing Writing for a Socially Just Future - Inoue, Asao B. (Open textbook library., 2015)
In Antiracist Writing Assessment Ecologies, Asao B. Inoue theorizes classroom writing assessment as a complex system that is "more than" its interconnected elements. To explain how and why antiracist work in the writing classroom is vital to literacy learning, Inoue incorporates ideas about the white racial habitus that informs dominant discourses in the academy and other contexts. Inoue helps teachers understand the unintended racism that often occurs when teachers do not have explicit antiracist agendas in their assessments. Drawing on his own teaching and classroom inquiry, Inoue offers a heuristic for developing and critiquing writing assessment ecologies that explores seven elements of any writing assessment ecology: power, parts, purposes, people, processes, products, and places.